The Leader Programme as an Impulse for New Projects in Rural Areas - Hoffmann, Robert; Hoffmann, Natalia (Quaestiones Geographicae, 2018)
The article aims to present the stages of the LEADER programme and its influence on greater activity and integration of inhabitants by, e.g. extending the knowledge of tradition and national heritage and the actions intended for the integration of local communities. It is noticeable particularly in the implementation of the activities within Axis 4 of the 2007–2013 Rural Development Programme. Positive changes in rural areas are a result of building strong social and human capitals, which are important factors of local development. The skills and the ability for cooperation of a local community allows it to implement many projects. The investments made by beneficiaries of the LEADER programme improve the level of living and the quality of life in the countryside. The effect is an improvement in physical infrastructure and tourist attractiveness as a result of care for the rural landscape and cultural heritage. The implementation of the LEADER programme is presented on the example of Wielkopolskie Voivodeship where the participation in actions for local communities is deeply ingrained. In order to show spatial differences in the activity of local entities under Local Action Groups in Wielkopolskie Voivodeship, classes were selected on the basis of funds received by local entities in the LAG areas. There are 36 Local Action Groups operating in Wielkopolska (of which 31 have seats in this region).